Dirucotide (MBP8298) for the treatment of multiple sclerosis. Issue 5 (September 2008) - Markowitz, Clyde
Multiple sclerosis (MS) is a chronic and debilitating disease affecting approximately 2.5 million people worldwide, and safe and effective treatment options are sorely lacking. While there are several currently approved drugs that have shown some efficacy at reducing the relapse rate in patients with the relapsing––remitting form of the disease, the impact of this outcome relative to long-term disease progression is unknown. Effective treatment for those with primary or secondary progressive MS is practically nonexistent. Dirucotide (MBP8298) is a synthetic peptide that has shown promise at increasing time to progression with little or no associated toxicity in Phase II studies. The drug is specifically designed to induce tolerance in patients with HLA types DR2 and/or DR4, although patients with other HLA subtypes may also benefit. Dirucotide is now being evaluated in two large Phase III secondary progressive MS trials, as well as a smaller Phase II relapsing––remitting MS trial.